Microstructural stability of long-term aged wrought Ni–Fe-based superalloys. Issue 10 (3rd July 2017) - Zhao, Xinbao; Dang, Yingying; Yin, Hongfei; Yuan, Yong; Lu, Jintao; Yang, Zhen; Yan, Jingbo; Gu, Yuefeng
ABSTRACT: The influence of long-term thermal exposure on the microstructure and microhardness of a new Ni–Fe-based superalloy, for advanced ultra-supercritical coal-fired power plants, was studied. Spherical γ ′ particles were coarsened with the increase of aging time, while the volume fraction of γ ′ was decreased. The amount of M23 C6 carbides was increased with aging time at 750°C, and the coarsening rate of the width of M23 C6 was consistent with that of the LSW model. The microhardness of the alloy was maintained following 935 h of aging time and then was slightly decreased. It was found that the transition from the strongly coupled dislocations model to the Orowan model was dependent on the size and volume fraction of γ ′.